Implementasi Teknologi Automatic Thermal Air Condition (ATAC) Berbasis Internet of Things (IoT) pada UKM Peternakan Ayam Broiler - Hasyim As'ari; Ikhwanul Qiram; Fuad Ardiyansyah (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Some problems caused covid-19 pandemic, one of serious impact for some bussiness sector as UKM farmer broiler chicken. The government policy to reduce covid-19 infection causes production process and broiler chicken marketing are hampered which is impact to reduce production omset farmer. Through community partnership program (PKM) has been expanded expenditious technology as Automatic Thermal Air Condition (ATAC) based on Internet of Things (IoT) and franchise system which are expected to be able to be problem solving faced by stocker farmer bioler chicken. The application result of ATAC based on IoT and system franchise significantly can raise farmer productivity through increasing chicken weight, reduce death rate and Feed Conversion Ratio (FCR), supported by right system franchise marketing proven to be able to increase farmer omset.